(untitled) (Experimental biology, 2009)
In experiments on mice it was shown that the fraction КФ:F1 of the extracellular metabolite of Fusarium solani fungus suppressed temperately the growth and development of Erlich solid carcinoma and had no effect upon the growth and development of Luis solid carcinoma